Fenótipo da cintura hipertrigliceridêmica e fatores nutricionais : um estudo com participantes do estudo longitudinal de saúde do adulto-Elsa-Brasil - Andrade, Juliana Rodrigues de (2016)
The hypertriglyceridemic waist phenotype (HWP) is used to identify individuals susceptible to cardiovascular risks that have changed markers. The objective was to investigate the association between fat and fiber intakes and HWP. Cross-sectional study conducted from baseline Study of Adult Health Longitudinal - ELSA-Brazil. Anthropometric and blood sampling was performed. Participants were classified according to presence of HWP when circumference ≥102 waist for men and women ≥88cm and triglicerídeos≥150mg/dL. Fat and fiber intakes was estimated from the Food Frequency Questionnaire. Socioeconomic, demographic and behavioral variables were collected in the questionnaire. We used the Kolmogorov-Smirnov test and later the Mann-Whitney test, Kruskal-Wallis test, chi-square and logistic regression model, with 5% significance. The presence of HWP was 16.4% in the population. Mean BMI, total cholesterol, HDL-C and LDL-C were, respectively, 26.6 ± 5.5kg/m2 214 ±4mg/dL, 57±1mg/dl and 131±3 mg/dL. There was no association between fiber and fat intakes with HWP. Men were less chance to have the HWP (OR=0.649, 95%CI=0.575 to 0.733) and participants who practiced low physical activity (OR=1.535, 95%CI=1.244 to 1.894), with a history of smoking (OR=1.525, 95 % =1.352 to 1.719), smoking (OR=1.543, 95% CI=1.307 to 1.816), which belonged the first (OR =1.461, 95% CI=1.275 to 1.675) and second tertiles income (OR=1.342; 95%CI=1.169 to 1.541), overweight (OR=6.587, 95%CI=5.372 to 8.078) and obesity (OR=21.789; 95%CI=17.844 to 26.606) were more chance. No association between fat and fiber intakes with HWP was found, although researchs have already demonstrated the effects of these factors on health.